1990
DOI: 10.1159/000125604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Delta-9-Tetrahydrocannabinol, Cannabinol and Cannabidiol, Alone and in Combinations, on Luteinizing Hormone and Prolactin Release and on Hypothalamic Neurotransmitters in the Male Rat

Abstract: The acute effects of low oral doses of Δ9-tetrahydrocannabinol (THC), cannabinol (CBN) and cannabidiol (CBD) administered alone or in combinations on LH and prolactin (PRL) secretion and on hypothalamic norepinephrine (NE), dopamine (DA) and serotonin (5-HI) dynamics were examined in adult male rats. Plasma LH levels were significantly reduced 60 min after administration of 0.5 mgTHC/kg body weight and 30, 60 and 120 min after administration of THC + CBN or THC + CBD. There were no changes in plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 17 publications
0
28
1
Order By: Relevance
“…Interestingly, in addition to dopaminergic neurons, THC also has been demonstrated to affect noradrenergic (47,48), serotonergic (49), and peptidergic neurons (50), including those of luteinizing hormone releasing hormone (LHRH), which are involved, directly or indirectly, in the mediation of sexual receptivity in female rodents (51,52). ICV administration of THC elevated LHRH content in the MBH within 30 min followed by a decrease at 60 min, concurrent with lowered plasma LH levels in male rats (53).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in addition to dopaminergic neurons, THC also has been demonstrated to affect noradrenergic (47,48), serotonergic (49), and peptidergic neurons (50), including those of luteinizing hormone releasing hormone (LHRH), which are involved, directly or indirectly, in the mediation of sexual receptivity in female rodents (51,52). ICV administration of THC elevated LHRH content in the MBH within 30 min followed by a decrease at 60 min, concurrent with lowered plasma LH levels in male rats (53).…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate both that the effect of Δ 9 -THC or anandamide stimulating ACTH secretion is mediated by a mechanism other than the activation of CB 1 receptors, and that these receptors are located in anterior pituitary cells other than corticotropes. Lactotropes would be one of the alternative candidates because of the marked effects of cannabinoids on PRL secretion [1, 2, 3, 4, 5, 7]. In addition, although previous studies demonstrated that Δ 9 -THC was unable to alter PRL secretion from incubated pituitary glands [27], thus indicating that the effects of cannabinoids on PRL secretion would be produced through the hypothalamus, we have preliminary evidence that anandamide affects PRL secretion in vitro from dispersed anterior pituitary cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of Δ 9 -tetrahydrocanabinol (Δ 9 -THC), the main psychoactive principle of Cannabis sativa preparations, or of other natural or synthetic cannabinoids, decreased prolactin (PRL) and gonadotropin secretion, but increased adrenocorticotropic hormone (ACTH) release from the anterior pituitary gland in rodents [1, 2, 3, 4, 5, 6, 7]. Moreover, anandamide, the first discovered endogenous ligand of cannabinoid receptors [8], is able to produce the same effects [7, 9, 10, 11, 12], thus indicating that endogenous cannabinoids may play a physiological role in neuroendocrine control.…”
Section: Introductionmentioning
confidence: 99%
“…The primary negative effects are ascribed to a hypothalamic action, although some of these down-regulating influences may be mediated directly at the level of the pituitary and the ovary. At systemic level, cannabinoids are able to modulate the hypothalamic-pituitary-gonadal axis and they have been shown to down-regulate blood LH levels, by indirectly modifying GNRH secretion (Murphy et al 1990). In vitro studies on rats have also demonstrated that D 9 -THC exerts a direct inhibitory effect on both folliculogenesis (Adashi et al 1983) and ovulation (El-Talatini et al 2008).…”
Section: The Endocannabinoid System and The Ovarymentioning
confidence: 99%